Pengaruh Intellectual Capital, Ukuran Perusahaan, dan Dewan Komisaris Independen terhadap Nilai Perusahaan - Finda Eka Azhari; Ani Kusumaningsih (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This study aims to analyze the effect of Intellectual Capital, Firm Size, and Independent Board of Commissioners on Firm Value in banking sub-sector companies listed on the Indonesia Stock Exchange for the period 2019–2023. The research employs a quantitative method with a panel data regression approach to assess the relationship between these variables. Purposive sampling was used to select a sample of 25 companies, resulting in a total of 125 observations. The data were collected from the companies' financial statements and annual reports, then processed using E-Views 12 software for analysis. The findings reveal that Intellectual Capital, Firm Size, and Independent Board of Commissioners simultaneously have a significant effect on Firm Value. However, when considered individually, Intellectual Capital does not show a significant impact on Firm Value, suggesting that intellectual assets may not be fully reflected in the value of the firms in the banking sub-sector. On the other hand, Firm Size and the presence of an Independent Board of Commissioners both have a significant positive effect on Firm Value, indicating that larger firms and those with independent governance structures tend to achieve higher firm value. These findings contribute to the understanding of corporate governance and intellectual capital in enhancing firm value, particularly in the banking industry.